Change of name for the Oriental robber fly Nyssomyia Hull, 1962 (Diptera: Asilidae, Asilinae), nec Nyssomyia Barretto, 1962 (Diptera: Psychodidae, Phlebotominae) - Ibáñez-Bernal, Sergio; Fisher, Eric (Zootaxa, 2015)
A new name for the Oriental genus Nyssomyia Hull, 1962 (Diptera: Asilidae) is proposed. Homonymy exists between this Oriental robber fly genus and the more senior Neotropical phlebotomine sand fly genus Nyssomyia Barretto, 1962 (sensu Galati 2003) (Diptera: Psychodidae), and the following replacement name is proposed: Ekkentronomyia nom. nov. for Nyssomyia Hull (nec Barretto 1962). Accordingly, a new combination is herein proposed for the only species currently included in this genus: Ekkentronomyia ochracea (Hull, 1962) comb. nov.